The Mythical Dimension in Saulius Tomas Kondrotas’ Novel “The Look of a Grass-Snake” - Mingilas, Vilius (Jaunųjų mokslininkų darbai, 2021)
The aim of the article is to identify and explain the mythical images used in Saulius Tomas Kondrotas’ novel “The Look of a Grass-Snake”. By transforming pagan and Christian mythical systems, the writer contrasts them with rational thinking. In “New Age“ there is no place for myths and the meanings of figurative language. The mythical dimension in the work is understood as a way of perceiving the world that contradicts the modern idea of ​​progress. S. T. Kondrotas also transforms the meanings of archetypal figures such as fire, sun or grass-snake in his novel. The concepts of life, death, or rebirth gain the different perspectives from archaic and modern world. New mythical dimension allows us to reconsider existential phenomena of human existence in a new light. In this way, the Baltic worldview extends its life in works of art, and the literature, which contains mythical elements, becomes a modern version of the myth.